The experiences of patients with amyotrophic lateral sclerosis of their decision‐making processes to invasive home mechanical ventilation—A qualitative study - Tina Thorborg; Jeanette Finderup; Dorte Skriver Winther; Charlotte Kirkegaard Lorenzen; Pia Dreyer (Nursing Open, 2023)
Abstract Aim To explore and gain knowledge of the experiences and needs among patients with amyotrophic lateral sclerosis (ALS) of their decision‐making processes whether to choose invasive home mechanical ventilation or not. Design A qualitative study. Methods A phenomenological‐hermeneutic approach influenced by Ricoeur's interpretation theory was used. Seven patients with ALS were interviewed. The Consolidated Criteria for Reporting Qualitative Research checklist was used for reporting. Results Three themes were evident in patients' accounts of the decision‐making process: (1) being taken care of directly after receiving the diagnosis, (2) living in uncertainty about what the future would bring and (3) doubt causing patients with ALS to change their minds. Patients with ALS were burdened with everyday life challenging decision‐making processes about future treatment and doubt caused patients to change their minds about their future treatment. It is necessary to support patients in their decision‐making processes using shared decision‐making. Patient or Public Contribution No Patient or Public Contribution.